1993
DOI: 10.1172/jci116440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endothelin receptor antagonist on cyclosporine-induced vasoconstriction in isolated rat renal arterioles.

Abstract: Recent evidence suggests that the potent constrictor peptide, endothelin (ET) has a mediating role in cyclosporine A (CsA)-related renal vasoconstriction. However, the nature of the CsA-ET interaction and effect on the renal vasculature is uncertain. The purpose of the present study was twofold: (a) to determine if CsA exposure caused direct local release of ET from the endothelium of the renal microvasculature and (b) to determine if locally generated ET has paracrine effects on the underlying vascular smooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
1
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(98 citation statements)
references
References 22 publications
(26 reference statements)
2
92
1
2
Order By: Relevance
“…CNI cause afferent arteriolar vasoconstriction by sympathetic stimulation and by upregulation of the local renin-angiotensin-aldosterone system. (10,11) CNI also decrease vasodilator prostaglandins and nitric oxide and increase vasoconstrictor cytokines (12,13). Glucocorticoids contribute to HTN by causing sodium and water retention.…”
Section: Cvd Risk Factors For Which There Is An Evidentiary Basis Formentioning
confidence: 98%
“…CNI cause afferent arteriolar vasoconstriction by sympathetic stimulation and by upregulation of the local renin-angiotensin-aldosterone system. (10,11) CNI also decrease vasodilator prostaglandins and nitric oxide and increase vasoconstrictor cytokines (12,13). Glucocorticoids contribute to HTN by causing sodium and water retention.…”
Section: Cvd Risk Factors For Which There Is An Evidentiary Basis Formentioning
confidence: 98%
“…It has been demonstrated that vasoconstriction is induced by activation of the renin-angiotensin system (RAS) and increase in levels of the vasoconstricting factors, endothelin and thromboxane, as well as suppression of synthesis of vasodilating prostacyclin, prostaglandin E2, and nitric oxide (NO) [9][10][11] . Interindividual susceptibility to cyclosporine-induced vasoconstriction also plays an important role 12 .…”
Section: Acute Arteriolopathymentioning
confidence: 99%
“…It is widely acknowledged that patients treated with the Cyclosporine and Cisplatin are at a high risk of developing nephrotoxicity [9,10]. Studies have demonstrated that Cyclosporine causes vasoconstriction of the afferent and efferent glomerular arterioles and reductions in renal blood flow and glomerular filtration rate [11,12]. Cisplatin is an important antineoplastic drug used for the treatment of cancers.…”
Section: Introductionmentioning
confidence: 99%